Passive sampling to capture the spatial variability of coarse particles by composition in Cleveland, OH. (March 2015) - Sawvel, Eric J.; Willis, Robert; West, Roger R.; Casuccio, Gary S.; Norris, Gary; Kumar, Naresh; Hammond, Davyda; Peters, Thomas M.
Abstract: Passive samplers deployed at 25 sites for three, week-long intervals were used to characterize spatial variability in the mass and composition of coarse particulate matter (PM10-2.5 ) in Cleveland, OH in summer 2008. The size and composition of individual particles determined using computer-controlled scanning electron microscopy with energy-dispersive X-ray spectroscopy (CCSEM-EDS) was then used to estimate PM10-2.5 concentrations (μg m −3 ) and its components in 13 particle classes. The highest PM10-2.5 mean mass concentrations were observed at three central industrial sites (35 μg m −3, 43 μg m −3, and 48 μg m −3 ), whereas substantially lower mean concentrations were observed to the west and east of this area at suburban background sites (13 μg m −3 and 15 μg m −3 ). PM10-2.5 mass and components associated with steel and cement production (Fe-oxide and Ca-rich) exhibited substantial heterogeneity with elevated concentrations observed in the river valley, stretching from Lake Erie south through the central industrial area and in the case of Fe-oxide to a suburban valley site. Other components (e.g., Si/Al-rich typical of crustal material) were considerably less heterogeneous. This work shows that some species of coarse particles are considerably more spatially heterogeneous than others in an urban area with a strong industrial core. It also demonstrates that passive sampling coupled with analysis by CCSEM-EDS is a useful tool to assess the spatial variability of particulate pollutants by composition. Graphical abstract: Highlights: Examined spatial variability of PM10-2.5 and components in Cleveland, OH. Used passive samplers with automated microscopy to classify particles. Components associated with steel and cement production highest in industrial area. Components associated with crustal material more uniformly distributed. Method may be useful to reduce exposure misclassification in epidemiological studies.